2021
DOI: 10.1126/science.aba2609
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of multispectral imaging with the AstroPath platform informs efficacy of PD-1 blockade

Abstract: Next-generation tissue-based biomarkers for immunotherapy will likely include the simultaneous analysis of multiple cell types and their spatial interactions, as well as distinct expression patterns of immunoregulatory molecules. Here, we introduce a comprehensive platform for multispectral imaging and mapping of multiple parameters in tumor tissue sections with high-fidelity single-cell resolution. Image analysis and data handling components were drawn from the field of astronomy. Using this “AstroPath” whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(118 citation statements)
references
References 48 publications
2
115
0
1
Order By: Relevance
“…Exploration of the prognostic value of the CG Signature method on datasets of other cancer types would surely be needed to verify its utility and capability. Additionally, future extension of the capability of CG Signature by using whole-slide images and other biomarkers in mIHC/mIF staining, for example, holds great potential for a more comprehensive analysis of the tumor microenvironment 15 ; this will in turn serve to better inform the training of more accurate GNN models. The continuing development of cutting-edge, robust, and broadly-applicable Cell Graph-based biomarker discovery algorithms is valuable and desirable to better inform and transform the medical care of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploration of the prognostic value of the CG Signature method on datasets of other cancer types would surely be needed to verify its utility and capability. Additionally, future extension of the capability of CG Signature by using whole-slide images and other biomarkers in mIHC/mIF staining, for example, holds great potential for a more comprehensive analysis of the tumor microenvironment 15 ; this will in turn serve to better inform the training of more accurate GNN models. The continuing development of cutting-edge, robust, and broadly-applicable Cell Graph-based biomarker discovery algorithms is valuable and desirable to better inform and transform the medical care of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the exploration of the TME of cancer samples would offer critical insights into the key spatial patterns associated with the growth, cancer progression, and thus patient prognosis 14 . Recent advent multiplexed immunohistochemistry (mIHC) staining technique enables systematic investigation of the TME 15,16 and supports extraction of enriched spatial information from the TME, including the cell location, cell types, cell and nucleus morphological information, and related optical information 14,17 . Researchers have applied the mIHC technique to analyze the TME of pancreatic cancer and found that spatial distribution of cytotoxic T cells in proximity to cancer cells correlates with increased overall patient survival 14 .…”
mentioning
confidence: 99%
“…On the other hand, a high density of rare cells such as CD8 + FoxP3 + PD-1-low T-cells are closely associated with long-term survival after anti-PD-1 blockade in malignant melanoma. 126 Prolonged antigen exposure and sustained inflammatory stimulations have been considered as potential mechanisms that may induce effector T-cells into an exhausted state. 127 Exhaustion of TILs has also been observed in HCC cases, and is correlated with poor clinical outcomes.…”
Section: Cellular Factors Involved In the Immune Suppressive Microenvironmentmentioning
confidence: 99%
“…Dans le domaine de l’astronomie, le traitement et l’analyse de plusieurs millions d’images multispectrales acquises par des milliers d’astronomes chaque année ont connu des avancées majeures au cours des dernières décennies. Appliquant les algorithmes astronomiques à l’anatomie pathologique, Berry et al ont développé une plateforme d’analyse de lames histologiques qu’ils appellent « AstroPath » [ 4 ]. Ainsi, ils ont mis au point une immunofluorescence multiplex en combinant six anticorps dirigés contre PD-1, PD-L1, CD163 (marqueur de monocytes/macrophages), Forkhead Box P3 (FoxP3) (marqueur de lymphocytes T régulateurs [Treg]), CD8 (marqueur de lymphocytes T effecteurs), Sox10/ S100 (marqueur de cellules tumorales de mélanome), et Di Aminido Phenyl lndol (DAPI).…”
Section: éLaboration De Marqueurs Pronostiques Composites Par Intelligence Artificielleunclassified